The Influence of Fundamental Analysis and Technical Analysis Towards the Prediction of Stock Price With Dividend Policy as Moderating Variable - FATMAWATI; Wira, Lestari; Friyani, Rita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of the research is to find out the relationship between fundamental analysis and technical analysis towards stock price. Fundamental analysis is interpreted by debt to equity ratio, earnings per share, current ratio, and return on assets. Technical analysis is interpreted by volume of trade and The Composite Stock Price Index. Furthermore, by applying dummy variable, dividend policy is applied as moderation variable to test the relationship between fundamental analysis towards the stock price as well as technical analysis towards the stock price. The population of the research is banking companies listed in IDX in 2019-2022. Technical analysis applied double regression analysis and moderated regression analysis (MRA) using SPSS 26. The finding of the research stated that technical analysis and fundamental analysis influence the stock price. Company policy to share dividend for the stock holders was proven to influence the relationship between those variables.